Systematic Review and Meta-Analysis of the Efficacy and Safety of Metformin and GLP-1 Analogues in Children and Adolescents with Diabetes Mellitus Type 2 - Elisabeth Carydias; Andoneta Tasho; Chara Kani; Flora Bacopoulou; Charikleia Stefanaki; Sophia L. Markantonis (MDPI AG, 2022)
Diabetes mellitus type 2 (DMT2) is one of the most frequent glucose metabolism disorders, in which serum glucose concentrations are increased. In most cases, changes in lifestyle and diet are considered as the first step in addressing its therapy. If changes in lifestyle and diet fail, drugs, such as metformin, must be added. Lately, apart from metformin or insulin, the FDA has approved the use of glucagon-like peptide-1 (GLP-1) analogues for children and adolescents. Little is known about their efficacy and safety at this young age. The main aim of this systematic review/meta-analysis was to assess the safety and efficacy of metformin and GLP-1 analogues, exenatide and liraglutide, compared with placebos or other antidiabetic drugs used for DMT2 in children and adolescents. Metformin did not seem to demonstrate pharmacologic superiority, while GLP-1 analogues were found superior to placebos. GLP-1 analogues may be considered a useful alternative for the treatment of DMT2 in children and adolescents.